(untitled) (Tarbiyah Suska Conference Series, 2022)
The purpose of this study is to determine the implementation of scientific integration in Islamic universities. Through a holistic education pattern that can raise awareness in individuals who study there is a link between science and divinity, the role of humans as caliphs on earth, diversity, morality, humanity, and the goals designed by God from its creation. Ciputat is a metropolitan city located between DKI Jakarta and South Tangerang. The role in educating the Muslim community can be seen where science is stretched, especially Islamic universities and Islamic colleges that have been established. Stages of this research method with a qualitative approach (qualitative research) by conducting research in the field (field research). The data collection techniques in the form of documentation, observation and instrumens. This research departs from the assumption that there has been a thought to integrate science in the design and thoughts of the leaders of the University of Muhammadiyah Jakarta, although there are differences in concepts and levels. The results of this study suggest that the scientific integration that has been implemented in tertiary institutions is theoretically through the efforts implemented by the leaders at the University of Muhammadiyah Jakarta. The implementation of scientific integration has been able to run intensively for the advancement of students at Muhammadiyah University, Jakarta. In addition, through this research, innovations made by educational units, especially Islamic Religious Colleges can be identified in improving the quality of students. This research has also issued recommendations on programs in higher education in lectures as an effort by lecturers to improve the quality of education through the integration of religious knowledge and general knowledge